Analisis Perilaku Pengelolaan Keuangan UMKM Selama Pandemi COVID-19 - Meri Mayang Sari; Desy Apriani; Nitia Inggarwati (UNIVERSITAS RAHARJA, 2022)
This study aims to determine the effect of financial literacy variables on the financial management behavior of SMEs. The research sample amounted to 100 respondents, namely MSMEs in the Kutabumi area. To obtain the data needed, the researcher distributed questionnaires to respondents using Partial Least Square (PLS) analysis and probability sampling method. This study shows that: (1) Financial literacy has no significant effect on the financial management behavior of MSMEs in the Kutabumi area during the COVID-19 pandemic, (2) MSME income in the Kutabumi area has a significant effect on MSME financial management behavior during the Covid-19 pandemic.